Perlindungan Hukum terhadap Konsumen Kesehatan di Kabupaten Jember - Tioma Roniuli Hariandja (Fakultas Hukum Universitas Islam Jember, 2013)
Malpractice health can be sued under the Consumer Protection Act. Because health care providers (a doctors / the medical / a hospital) can be referred to as entrepreneurs by the Consumer Protection Act (UUPK) in conjunction with Pasal 1 angka 3 of Act No. 23 Tahun 1992 about Health juncto ministr of health No.756/MENKES / SK/VI/2004 about preparation liberalization of trade and the health sector. While users of health care or the patient can be referred to as the health of consumers by the Consumer Protection Act Pasal 1 angka 2. However lawsuit against maids health services is still relatively rare this is due to the pattern of paternalistic relationships, where the consumer / patient let go against all actions performed medical doctors / para medical / hospital.